1989
DOI: 10.1159/000120432
|View full text |Cite
|
Sign up to set email alerts
|

The Cause of Chiari II Malformation: A Unified Theory

Abstract: The cause of the Chiari II hindbrain deformity in children born with a myelomeningocele can be explained by the lack of distention of the embryonic ventricular system. Defective occlusion and an open neural tube precludes the accumulation of fluid and pressure within the cranial vesicles. This distention is critical to normal brain development. The small posterior fossa, cerebral disorganization, and lückenschädel are the result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
245
0
7

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 483 publications
(260 citation statements)
references
References 40 publications
8
245
0
7
Order By: Relevance
“…A failure to maintain this driving pressure in patients with open neural tube defects has been proposed as a mechanism for the genesis of the Chiari malformation. 37 …”
Section: Occlusion Of the Spinal Neurocelementioning
confidence: 99%
“…A failure to maintain this driving pressure in patients with open neural tube defects has been proposed as a mechanism for the genesis of the Chiari malformation. 37 …”
Section: Occlusion Of the Spinal Neurocelementioning
confidence: 99%
“…Boyles reported that the volume of the posterior fossa was "highly heritable" (7). Embryologically, the Chiari malformation has been described as a mesodermal deficiency (30) and as a neuroectodermal failure (4,26,27). Gripp, however, proposes that displacement of the cerebellar tonsils may be due to osseous and cartilaginous abnormalities instead of being the result of embryological disturbances (19).…”
Section: █ Discussionmentioning
confidence: 99%
“…The exact causal relationship between the Chiari II malformation and hydrocephalus has only recently begun to be well understood. [5][6][7] Recent data show a decrease in the rate of Chiari II malformation and subsequent hydrocephalus in patients in whom the spinal defect is repaired in utero. [8][9][10] However, this remains controversial.…”
Section: Pathogenesismentioning
confidence: 99%